Romantic Elements in the March Family in the film Little Woman (2019): Philosophy Perspective - Alfiyani, Rahma; Sumayah, Sumayah (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to identify the indicators of romantic love, describe how romantic love is reflected, and explain why these elements are exposed in the film Little Women (2019) from a philosophical perspective. The research focuses on the emotional relationships within the March family, encompassing love, togetherness, sacrifice, and freedom among the sisters in various relationship dynamics. The study identifies six key elements of romanticism: love as an expression of deep emotion, freedom in love, the sublimity of love through nature, love as a process of self-discovery, tragic and unrequited love, and sacrifice in love. These elements are elaborated through the analysis of the main characters' interactions, such as Jo, Laurie, Meg, and Amy, which reflect the complexity of human emotions. The findings reveal that love in this film is a transformational experience, involving not only happiness but also sacrifice, freedom, and emotional journeys in self-discovery. This study provides new insights into how elements of romanticism enrich family dynamics and emotional values, making the film a significant subject for further exploration within the context of romanticism philosophy.